PENGARUH BIODELIGNIFIKASI DAUN SAWIT MENGGUNAKAN KAPANG Phanerochaete Chrysosporium YANG DISUPLEMENTASI DENGAN MINERAL CA TERHADAP KARAKTERISTIK CAIRAN RUMEN SECARA In Vitro - Sri, Rahayu (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Jabal Ghafur, 2020)
The aims of this research to see the effect of biodelignification of palm leaves using Phanerochaete chrysosporium againts total VFA, NH3 and pH. This study used factorial randomized block design (4x3) with 3 replications. Factor A is a dose of mineral addition in which A0 = 0 ppm Ca mineral, A1 = 1000 ppm Ca mineral, A3 = 1500 ppm Ca mineral, and A4 = 2000 ppm Ca mineral. Factor Y is the time of fermentation Y1 = 10 days, Y2 = 15 days, and Y3 = 20 days. Fermentation of palm leaves using Phanerochaete chrysosporium at a dose of Ca 2000 ppm mineral with a fermentation time of 10 days showed a total of 121.25 mM VFA more than any other treatment, and the amount of NH3 produced 14.80 mg / 100 ml of rumen fluid, and pH ranges from 6.79 to 6.86. The resulting pH is still in a condition where rumen microbes can grow optimally.Keywords: Biodelignification, Phanerochaete chrysosporium, NH3, pH, Volatille Fatty Acid (VFA)